A Brief Analysis of Errors and Their Causes of Indonesian Students Learning Chinese Characters 浅析印尼留学生学习汉字的偏误及原因 - Lydia Anggreani (Humaniora, 2015)
Chinese characters are symbols of written notation system. It is the carrier of heritage and development of Chinese cultural. Teaching Chinese as a foreign language is a new discipline that has rapidly developed, but Chinese characters are difficult to be taught and write. For bahasa Indonesia doesn't have any relation with Mandarin, it is easy to make mistake in learning Mandarin. When Indonesian students learned Chinese characters, they found that Chinese characters were one of the difficulties. Some of the students realized the importance of Chinese characters. They had learned every day, but the results were not ideal. Because some of the students did not learn very well in Chinese word, it affected their improvement in their listening, speaking, reading, and writing skill, also it affected their interest in learning Chinese. Nevertheless, some students found that Chinese characters were very hard so it pushed them to try harder in learning Mandarin and this kind of effort made them get good result; hence, it actually had some psychology effect. Research was done onIndonesian born Chinese that study abroad. Data collection was gathered from student’s exercises, homeworks, and exams. The result of the research is that Indonesian born Chinese usually didn't follow the right stroke in when learning Chinese characters.